2003
DOI: 10.1177/0095798403254210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Workplace Monitoring Policies on Potential Employment Discrimination and Organizational Attractiveness for African Americans in the Technical Professions

Abstract: Many organizations have policies concerning the use of technology to monitor the communications of employees. The present study explored the effects of these policies on beliefs and preferences of Black job applicants. Using a simulated job advertisement, we varied organizational monitoring policies and application submission methods in a 2 × 2 between-subjects experiment with 600 participants from a professional organization of Black engineers. Using a multiple stakeholder model of organizational privacy as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
2
7
0
1
Order By: Relevance
“…The 25 behavioural intention items for the present study were developed according to the strategy described by Ajzen and Fishbein (1980). Item content was derived from open‐ended interview studies reported by Stanton and Weiss (2000, 2003). Item development was also guided by the literature on workplace deviance (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 25 behavioural intention items for the present study were developed according to the strategy described by Ajzen and Fishbein (1980). Item content was derived from open‐ended interview studies reported by Stanton and Weiss (2000, 2003). Item development was also guided by the literature on workplace deviance (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the reliance of organizational MST implementation on employee acceptance and compliance, very few studies in the domain of MST examine employees' acceptance and compliance with MST policies and practices as an outcome variable. Studies that investigated outcomes of MST from an employee perspective have examined whether the implementation or presence of MST policies and practices impacts perceptions of fairness and justice (Alge, 2001; Douthitt & Aiello, 2001; Hovorka‐Mead, Ross, Whipple, & Renchin, 2002; Stanton, 2000), privacy concerns (Alge, 2001; Hovorka‐Mead et al , 2002), task and job performance (Aiello & Kolb, 1995; Larson & Callahan, 1990; Stanton & Barnes‐Farrell, 1996; Stanton & Julian, 2002; Stanton & Sarkar‐Barney, 2003), organization attraction and turnover (Hovorka‐Mead et al , 2002; Stanton & Lin, 2003), and employee well‐being and job stress (Aiello & Kolb, 1995; Douthitt & Aiello, 2001; Holman, Chissick, & Totterdell, 2002). Among the few studies that have explicitly investigated acceptance of monitoring systems as a necessary prerequisite for their functioning are studies on acceptance and use of active badge monitoring systems (Harper, 1995), and awareness monitoring systems (Zweig & Webster, 2002, 2003).…”
mentioning
confidence: 99%
“…Stanton (2003) showed that failing to protect privacy made the organization seem less attractive as an employer, and potentially a source of discrimination among black applicants who, as a group, have historically experienced employment discrimination. Mastrangelo and Popovich (2000) showed that employees perceived that their organizations' drug testing invaded their privacy, which was related to turnover intentions.…”
Section: Resultsmentioning
confidence: 99%
“…(2003) ise web sitesinin kullanışlılığının adayları etkilediğini ifade etmiştir. Bu süreçte gizlilik ihlalinin gerçekleşmesi ise, örgütün daha az çekici hale gelmesine neden olmaktadır (Stanton & Lin, 2003).…”
Section: öRgütsel çEkicilik Ve Algılanan Birey-örgüt Uyumu İlişkisi: üNiversite öğRencileri üZerine Bir Araştırmaunclassified